Optimizing Critical Thinking Skills of Vocational Students: Integrating Project-Based Learning with Learning Style Diversity - Inda Annisa; Novia Trisanti (Language and Education Journal, 2026)
Critical thinking is the 21st-century cognitive competency that current graduates clearly require to adapt to global changes in the world of work and technology. This skill plays a crucial role in helping students process information logically and solve problems rationally. Therefore, a learning model that focuses on developing higher-order thinking skills is needed. This study aims to examine the extent to which project-based learning influences the enhancement of students’ critical thinking skills based on their learning style. This study adopts a quantitative approach with a true experimental design. There were 52 vocational high school students as participants, who were separated into an experimental class and a control class. The study used an independent sample t-test of post-test score and N-gain score to address its research questions with a significance level of 0.05. The result of the t-test showed (t = 3.11; p = 0.003 < 0.05), which means that the post-test score for the experimental class was 84.00 higher than the control class, which was 79.76. Meanwhile, the N-gain score showed a score of 0.67, which means that the effectiveness of the learning model used at the medium level is considered effective enough. These findings emphasized that integrating project-based learning with diverse learning styles contributes significantly to developing critical thinking skills of students, especially for the kinesthetic learning style. Critical thinking skills enhancement is reflected in the project implementation stage, where students actively analyze and compile information in infographic projects that are aligned with their learning styles.